THE EFFECT OF SIMPLE BELL ALARM USAGE ON NURSE’S JOB SATISFACTION LEVELS IN THE RESUSCITATION ROOM OF THE EMERGENCY DEPARTMENT - Seputra, Sundawam Priyo; Setiawan, Arif Helmi; Hatmanti, Nety Mawarda; Faizah, Imamatul (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: The Emergency Room (ER) of ER of Haji Surabaya General Regional Hospital consists of many partitions, but there is no code blue activation. The ER staff use the methods by phone calling or shouting, if they need a request for assistance in handling resuscitation patients. The team has the potential to feel dissatisfied with the infrastructure at work. Objective: The purposes of this research is to analyse the effect of using a simple alarm bell on the job satisfaction of nurses in the emergency room resuscitation. Methods: The research design used the Pre-Experimental method (One Group Pretest-Posttest). The population in this study were all nurses in the emergency room at the ER of Haji Surabaya General Regional Hospital in Surabaya, totaling 34 nurses. Using the total sampling technique, a sample of 31 nurses was obtained. The independent variable is the simple use of the alarm bell, and the dependent variable is the level of nurse satisfaction. Data collection tool using a job satisfaction level questionnaire. Data analysis using the Wilcoxon test. Result: The results of data analysis using the Wilcoxon sign rank test yielded a value of p = 0.051 (0.051> 0.05) then H0 was rejected, which means that there was no significant difference between the level of job satisfaction of nurses before and after using a simple alarm bell. However, the results of the analysis of the average level of satisfaction before and after using the simple bell alarm were 24.52 and 25.35 points. In the total number of assessments, it was found that the average level of satisfaction after using the simple bell alarm was greater than the average level of satisfaction before using the simple bell alarm, there was a difference of 0.83 points. Conclusion: The results of this study can be concluded that Job satisfaction of all nurses in the emergency resuscitation room before using the simple bell alarm was satisfied. Job satisfaction of all nurses in the emergency resuscitation room after using the simple bell alarm was satisfied. There is no significant difference between the level of job satisfaction before and after using the simple alarm bell, but there is an increase in nurse satisfaction points descriptively with the infrastructure that supports their work. The use of a simple alarm bell in this study should be evaluated periodically by the nursing department in the hospital in order to determine its effectiveness in patient care.